Effect of Cell-Free DNA Screening vs Direct Invasive Diagnosis on Miscarriage Rates in Women With Pregnancies at High Risk of Trisomy 21: A Randomized Clinical Trial. Issue 1 (January 2019) - Malan, Valérie; Bussières, Laurence; Winer, Norbert; Jais, Jean-Philippe; Baptiste, Amandine; Le Lorc'h, Marc; Elie, Caroline; O'Gorman, Neil; Fries, Nicolas; Houfflin-Debarge, Véronique; Sentilhes, Loic; Vekemans, Michel; et al.
Abstract : (Abstracted from JAMA 2018;320(6):557–565) Cell-free DNA (cfDNA) tests are increasingly offered to women at increased risk of trisomy 21 to decrease the number of required invasive fetal karyotyping procedures and their associated miscarriages. The effect of this strategy has not been evaluated prospectively when compared with invasive diagnostic testing.